Treinamento intervalado de alta intensidade associado a reavaliação cognitiva no afeto positivo e negativo: ensaio clínico, randomizado - Souza, Irinaldo Capitulino de (2023)
Positive affect is the subjective experience of positive emotional states, such as pride, interest and happiness, which are distinguished from positive emotions, although they are interrelated concepts. On the other hand, negative affect is associated with the manifestation of negative mood states, which encompass emotions such as fear, sadness, disgust and anguish. Previous research indicates that the combination of high-intensity interval training (HIIT) associated with emotional regulation strategy, specifically cognitive reassessment, has the potential to increase positive affect, experiments in laboratory environments. However, there is still uncertainty about the ability of this association to potentiate positive affect in protocols conducted in online and synchronous format. The objective of the study was to investigate and evaluate the effects of high-intensity interval training (HIIT) associated with cognitive reassessment strategy on positive and negative affects in sedentary young women in online and synchronous format. This is a randomized controlled clinical trial, conducted in online and synchronous format, with the participation of 61 women. For data collection, an online form was used as a data collection instrument, consisting of seven different questionnaires: a) Sociodemographic questionnaire, b) Positive and negative affect (PANAS), c) Emotional regulation questionnaire (QRE)d) Perceived exertion scale (BORG-CR10), e) Emotional regulation difficulties scale, f) Depression, anxiety and stress test (DASS-21) and g) Manikin self-assessment (SAM scale). The results presented in this study demonstrate that the high intensity interval training group (M=42; SD=2) presented a mean score of positive affect significantly different from the mean scores of the placebo groups (M=30; SD=4; p<0.0001), cognitive reassessment (M=25; SD=5; p<0.0001) and high intensity interval training associated with cognitive reassessment (M=35; SD=4; p<0.0001). In addition, in the interval training group associated with cognitive reassessment (M=35; SD=4; p<0.0001) the mean positive affect score was significantly different from the cognitive reassessment groups (p-value < 0.0001). These results are in line with different studies produced internationally on interval training and emotional regulation and positive and negative affect, contributing to these areas of research.